2017
DOI: 10.4013/nbc.2017.122.01
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial fauna of the largest granitic cave from Southern Hemisphere, southeastern Brazil: A neglected habitat

Abstract: Studies focusing cave fauna on granitic caves are relatively rare when compared to carbonatic ones and no one considered replicas in the sampling to test fauna distribution patterns. We describe the terrestrial fauna of Riacho Subterrâneo cave through four sampling occasions (replicas) in different seasons. We analyzed seasonality and substrate preference of terrestrial invertebrates and discussed the importance of this neglected habitat as a refuge for fauna. Furthermore, we stressed the importance of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…In this frame, our data emphasize the fact that the study of cave twilight zone communities should preferably incorporate a temporal perspective, as already suggested by other authors (e.g. Culver and Sket 2002, Bichuette et al 2017, Lunghi et al 2017.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this frame, our data emphasize the fact that the study of cave twilight zone communities should preferably incorporate a temporal perspective, as already suggested by other authors (e.g. Culver and Sket 2002, Bichuette et al 2017, Lunghi et al 2017.…”
Section: Discussionsupporting
confidence: 82%
“…However, evidences have accumulated testifying that subterranean habitats are not entirely aseasonal Culver 1969, Tobin et al 2013), and that their inhabitants are not entirely arhythmic (Friedrich 2013, Abhilash et al 2017. Most subterranean habitats are indeed characterized by a constant flux of invaders and migrants (Chapman 1993, Culver and Sket 2002, Culver and Pipan 2009, Romero 2009, and there can be a temporal variability in the presence and distribution of vertebrates (e.g., Reichard et al 2009, Krofel 2010, Biswas 2014, Baker 2015, Ineich and Bourgoin 2016, Balogová et al 2017, Lunghi et al 2018) and invertebrates (e.g., Crouau-Roy et al 1992, Gnaspini et al 2003, Novak et al 2004, Papi and Pipan 2011, Tobin et al 2013, Mammola and Isaia 2014, Bento et al 2016, Mammola et al 2015, 2016a, Bichuette et al 2017, Lunghi et al 2017, Plăiaşu et al 2017 found in caves. For instance, invertebrates may move in search of food in larger cave chambers, and move back to the more stable fissures connected with caves in response to any physiological stress (Juberthie 1969, Chapman 1985.…”
Section: Introductionmentioning
confidence: 99%
“…species exploiting subterranean habitats in certain phases of their life cycle (Diesel et al 1995, Polak 1997, Culver and Sket 2002, Glover and Altringham 2008, Novak et al 2010a, Chelini et al 2011, Polseela et al 2011, Baker 2015, Lipovšek et al 2016. As a direct consequence, there can be conspicuous temporal turnovers in the species composition in a typical subterranean community (Nitzu et al 2011, Bento et al 2016, Yun et al 2016, Bichuette et al 2017, especially in the vicinity of the surface (Rendoš et al 2012) which should be taken into account when designing ecological studies and sampling protocols (Culver and Sket 2002, Meleg et al 2015, Wynne et al 2018). For instance, different arthropods may actively move from larger cave chambers to the stable network of fissures and vice versa (Chapman 1985), or rearrange their spatial distribution along the cave length in different seasons (Crouau-Roy et al 1992, Mammola et al 2015a, 2017a, Lunghi et al 2017.…”
Section: Community Turnovermentioning
confidence: 99%
“…For instance, different arthropods may actively move from larger cave chambers to the stable network of fissures and vice versa (Chapman 1985), or rearrange their spatial distribution along the cave length in different seasons (Crouau-Roy et al 1992, Mammola et al 2015a, 2017a, Lunghi et al 2017. As a direct consequence, there can be conspicuous temporal turnovers in the species composition in a typical subterranean community (Nitzu et al 2011, Bento et al 2016, Yun et al 2016, Bichuette et al 2017, especially in the vicinity of the surface (Rendoš et al 2012) which should be taken into account when designing ecological studies and sampling protocols (Culver and Sket 2002, Meleg et al 2015, Wynne et al 2018).…”
Section: Community Turnovermentioning
confidence: 99%
“…Besides this, only a few approaches covered long-term samplings, with replicas enough to contemplate more than one annual cycle (e.g. Trajano 1991, Resende and Bichuette 2016, Zepon and Bichuette 2017. Most often in tropical caves, the seasonal oscillation is of great importance in the dynamics of the subterranean environments (Trajano 2000).…”
Section: Introductionmentioning
confidence: 99%